A study of the most common complications encountered by the UPCD clinicians in the clinics (ENDO. - O.S. Sections) during chairside treatment - Banaag, Alberto R.; Zulueta, Josephine J.; Javier, Maria Cristina O. (Adviser).
A survey was conducted among the senior clinicians of UPCD class of1985 concerning the complications which they have encountered during chairside treatment in Endodontics and Oral Surgery sections and their perceived causes. A self-administering questionnaire was distributed among the population concerned and results showed that for Endodontics, the 3 most common complications encountered by UPCD senior clinicians during chairside treatment are obstruction of the canal (dentinal plug), ledge formation and over instrumentation. For Oral Surgery, the most common complications associated with tooth removal are fracture of the tooth, injury to the lips, cheek and tongue, and difficulty of access. Most clinicians attributed these complications to 3 major causes or factors, namely: carelessness and negligence, inadequate training/skill and poor equipment/facilities.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Endodontics; Surgery, Oral -- Complications